CONTROL AND EVALUATION ACTIVITIES IN MATHEMATICS LESSONS - Khayitova Sarvinoz Valijon qizi (Scholar Express Journal, 2023)
In today's time, we can observe a decrease in results in mathematics on the GIA and USE, associated, according to teachers, with low motivation of students to study. This article discusses the possibility of increasing interest in teaching and the level of training of schoolchildren using a system of control and assessment of knowledge. The article reveals the essence of control and evaluation activities and their types. Various examples of training work are given
Keywords: Types of control; control and evaluation activities; independent work